RECYCLING OF OIL USED FOR THE PRODUCTION OF HANDMADE LIQUID SOAP AS AN EXPERIMENTAL ACTIVITY IN CHEMISTRY - da Silva, Moisés (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to carry out a reflective analysis on the production process of homemade liquid soap from the waste of cooking oil generated. Every day, it becomes more evident to the population how much the commitment we must have with the care of the environment is necessary, as there are a number of problems that oppose the existence of a healthy environment, among these are those arising from the practices of everyday life such as the poor disposal of cooking oil after use, whose final destination, in most cases, are sink drains, causing their clogging, the gullets of large urban centers, damaging the bodies of water and causing in environmental problems such as pollution of the aquatic environment and economic losses such as the increase in the cost of processes in effluent treatment plants. Through this practical-experimental activity, it is understood that teaching Chemistry through experimentation develops logical reasoning, stimulates thinking, creativity and the ability to resolve situations related to the content, which will be linked to the reality of everyday life there. students, from a formative and citizen perspective. In addition, making use of an approach that involves current issues and content of general interest, it helps the student to understand Chemistry in its daily applications, awakening him to value the sciences and motivating him to search for new knowledge.